2010
DOI: 10.1007/s11262-010-0507-2
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated evolution of PRRSV during recent outbreaks in China

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is reported to have evolved at a higher evolutionary rate than other RNA viruses. However, whether this virus is capable of evolutionary acceleration during outbreaks remains unknown. In this study, we analyze the data based on ORFs of eight newly obtained epidemic PRRSVs from Hebei province with other viral genomes from GenBank. Phylogenetic analysis suggested that all isolates during recent outbreaks (2006-2008) are grouped together. We also find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…That is, the nonsynonymous/ synonymous substitution ratio (x = dN/dS) value of the complete ORF 5 to 7 sequences from 150 global PRRSVs was 0.2229: 0.2372 for EU-type isolates and 0.2914 for NA-type isolates. This point confirms the views of Pesch et al [25], while it contradicts the predictions of others such as Hanada et al [14] and Song et al [33], who demonstrated that the evolution of PRRSV was driven by positive selection. The exchange of different genetic sites between viruses by recombination, however, contributes to PRRSV genetic diversity and evolution, although in the present study, no pattern of recombination events was detected that was consistent across all PRRSVs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…That is, the nonsynonymous/ synonymous substitution ratio (x = dN/dS) value of the complete ORF 5 to 7 sequences from 150 global PRRSVs was 0.2229: 0.2372 for EU-type isolates and 0.2914 for NA-type isolates. This point confirms the views of Pesch et al [25], while it contradicts the predictions of others such as Hanada et al [14] and Song et al [33], who demonstrated that the evolution of PRRSV was driven by positive selection. The exchange of different genetic sites between viruses by recombination, however, contributes to PRRSV genetic diversity and evolution, although in the present study, no pattern of recombination events was detected that was consistent across all PRRSVs.…”
Section: Discussionsupporting
confidence: 77%
“…Most recently, Shi et al [32] estimated a mean evolutionary rate of 1.46 9 10 -3 substitutions/site/ year for ORF 5 data and noted that the common ancestors of genotype NA viruses appeared approximately in 1979 (1977)(1978)(1979)(1980)(1981)(1982). Additionally, Song et al [33] used ORF 5 sequences of two genotypes and demonstrated that the mean evolutionary rates of PRRSVs were 3.29 9 10 -3 and that the virus diverged in 1894. Our findings on this topic do not support the previous suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…According to our analysis, the T MRCA of sub-lineage 5.1 strains was approximately 17 years ago, which is supported by serological evidence for anti-PRRSV antibodies in Vietnam during this time. The T MRCA of sub-lineage 8.7 strains was estimated to have occurred in 2002, which is similar to the T MRCA of the HP-PRRSV from China [36]. …”
Section: Discussionmentioning
confidence: 92%
“…Further analysis of the whole PRRSV genome shows that the two types of PRRSV diverged from a common ancestor about 800 years ago [46]. Furthermore, genetic analyses indicate that the evolutionary trends, antigenic characteristics, and genetic diversity of PRRSV in different regions have distinct patterns [6, 11, 17, 32, 36, 40]. …”
Section: Introductionmentioning
confidence: 99%
“…Most Chinese isolates belong to the American genotype and can be further classified into four subgroups based on the whole genome (1,5). Under the immune pressure caused by the current control strategy, in which attenuated vaccines are widely used, PRRSVs are geared for rapid variation through mutation or recombination (6,7,11,14), resulting in new isolates with different levels of pathogenicity and virulence.…”
mentioning
confidence: 99%